Impact of the commercial law on e-commerce practices and business sustainability in Nigeria - Daniel E. Ufua; Olusola J. Olujobi; Mamdouh Abdulaziz Saleh Al-Faryan (International Journal of Management, Economics and Social Sciences (IJMESS), 2023)
With the advent of global market interdependence and interaction, coupled with the consistent spread of the internet facilities across geographical boundaries, businesses engage in e-commerce practices either to augment existing on-ground businesses or as independent outfits. This study focused on the law on e-commerce practice and business sustainability in Nigeria. The study applied a conceptual review focusing on the trends of development of e- commerce practice and the supportive effects of the legal system in facilitating business sustainability in Nigeria. The study relied on extant literature sourced from various outlets, relevant to the topic of this study. The key findings highlighted and discussed factors for improved e-commerce practices in Nigeria. These included access to legal services, effective government policy and institutional support, time and fair interpretation of the law governing e-commerce, continuous evaluation of the e- commerce processes in Nigeria, increased awareness and familiarity with e-commerce facilities, and the adoption of suitable technology. The study provides valuable insight into the support of the Nigerian commercial sector on e-commerce practices. The adoption of systems theory enhances the promotion of fairness across the entire ambience of e-commerce practice and the support of the law. This implied focusing on the continuous evaluation of legal support and a flexible process of developing the needed approaches to address emerging changes in e-commerce that can enhance business sustainability in Nigeria.
Keywords: K39; M38; 330; Business sustainability; flexible process; government policy; legal system support; Nigerian economy